2017
DOI: 10.1162/jocn_a_01149
|View full text |Cite
|
Sign up to set email alerts
|

Different Electrophysiological Correlates of Visual Awareness for Detection and Identification

Abstract: Detecting the presence of an object is a different process than identifying the object as a particular object. This difference has not been taken into account in designing experiments on the neural correlates of consciousness. We compared the electrophysiological correlates of conscious detection and identification directly by measuring ERPs while participants performed either a task only requiring the conscious detection of the stimulus or a higher-level task requiring its conscious identification. Behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
82
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 37 publications
15
82
6
Order By: Relevance
“…Another explanation is that spatial frequency was lower in previous studies (three lines spanning a square of 1.5°) than in the Koivisto and Grassini study (10 c/deg), and N1 amplitudes increase with spatial frequency of high-contrast Gabors (Mihaylova, Hristov, Racheva, Totev, & Mitov, 2015 ). Notably, a recent study showed that VAN varies with the calibration threshold such that VAN was observed at the detection threshold but not the identification threshold (Koivisto, Grassini, Salminen-Vaparanta, & Revonsuo, 2017 ). In the study, awareness was calibrated separately to the detection and identification thresholds with the same subjective rating scale: “I did not see any stimulus,” “I saw something (but could not identify the stimulus),” “I saw the stimulus almost clearly (and could identify it),” and “I saw the stimulus clearly (and could identify it).” In a detection task, stimuli were calibrated to be rated as “I did not see any stimulus” in about 50% of the trials (not aware of the stimulus).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that spatial frequency was lower in previous studies (three lines spanning a square of 1.5°) than in the Koivisto and Grassini study (10 c/deg), and N1 amplitudes increase with spatial frequency of high-contrast Gabors (Mihaylova, Hristov, Racheva, Totev, & Mitov, 2015 ). Notably, a recent study showed that VAN varies with the calibration threshold such that VAN was observed at the detection threshold but not the identification threshold (Koivisto, Grassini, Salminen-Vaparanta, & Revonsuo, 2017 ). In the study, awareness was calibrated separately to the detection and identification thresholds with the same subjective rating scale: “I did not see any stimulus,” “I saw something (but could not identify the stimulus),” “I saw the stimulus almost clearly (and could identify it),” and “I saw the stimulus clearly (and could identify it).” In a detection task, stimuli were calibrated to be rated as “I did not see any stimulus” in about 50% of the trials (not aware of the stimulus).…”
Section: Discussionmentioning
confidence: 99%
“…This low rate was expectable because the contrast of the stimulus was individually calibrated to a level where 50% or slightly less of the subjective responses were ‘saw nothing’. In our previous study using 4-point PAS [ 31 ], the contrast of Gabor patches was calibrated in detection task to a level in which about 50% of the stimuli received the lowest rating (‘saw nothing’). In the actual experiment, the distribution of ratings was such that ‘nothing’ was seen in 55% of trials, ‘something’ was seen in 40% of trials, ‘almost clear’ perception was present in 3% of trials, and ‘clear’ perception in 2% of trials.…”
Section: Discussionmentioning
confidence: 99%
“…We calibrated the contrast for each participant individually such that about 50% of the primes, or slightly less, would be rated as completely invisible under CFS. Under such presentation condition, we expect on basis of our earlier experience [ 31 ] that the participants would never or very rarely see the prime clearly and they would use predominantly the ‘saw nothing’ and ‘saw something’ alternatives. Therefore, we modified the subjective scale to be more consistent with participants’ experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate line of research (Genetti et al 2009; Tanskanen et al 2007), neural responses associated with awareness of facial identity are found to emerge relatively late around 230 ms and this effect is followed by an increase of the P300 component. The notion that conscious face detection precedes conscious face identification is further supported by a recent study on object perception (Koivisto et al 2017). In this study, stimulus hierarchy is taken into account by comparing electrophysiological correlates between two separate tasks, in which participants were required to detect the presence of a digit stimulus at threshold or to identify whether the digit was smaller or larger than 5.…”
Section: Introductionmentioning
confidence: 75%